Еврипид - Гончарова Татьяна Викторовна (Жизнь замечат. людей : ЖЗЛ : Сер. биогр.: Осн. в 1933 г. М. Горьким, 1986)
Экземпляры: ф. 2 (20140214) / Инвентарный номер: 100694 / Авт.знак: Г 65 / ГРНТИ: 17 / ББК: 83.3(0)3